PERK-mediated antioxidant response is key for pathogen persistence in ticks - Kristin L. Rosche; Joanna Hurtado; Elis A. Fisk; Kaylee A. Vosbigian; Ashley L. Warren; Lindsay C. Sidak-Loftis; Sarah J. Wright; Elisabeth Ramirez-Zepp; Jason M. Park; Dana K. Shaw (mSphere, 2023)
ABSTRACT A crucial phase in the life cycle of tick-borne pathogens is the time spent colonizing and persisting within the arthropod. Tick immunity is emerging as a key force shaping how transmissible pathogens interact with the vector. How pathogens remain in the tick despite immunological pressure remains unknown. In persistently infected Ixodes scapularis, we found that Borrelia burgdorferi (causative agent of Lyme disease) and Anaplasma phagocytophilum (causative agent of granulocytic anaplasmosis) activate a cellular stress pathway mediated by the endoplasmic reticulum receptor PKR-like ER kinase (PERK) and the central regulatory molecule eIF2α. Disabling the PERK pathway through pharmacological inhibition and RNA interference (RNAi) significantly decreased microbial numbers. In vivo RNAi of the PERK pathway not only reduced the number of A. phagocytophilum and B. burgdorferi colonizing larvae after a bloodmeal but also significantly reduced the number of bacteria that survive the molt. An investigation into PERK pathway-regulated targets revealed that A. phagocytophilum and B. burgdorferi induce activity of the antioxidant response regulator, nuclear factor erythroid 2-related factor 2 (Nrf2). Tick cells deficient for nrf2 expression or PERK signaling showed accumulation of reactive oxygen and nitrogen species in addition to reduced microbial survival. Supplementation with antioxidants rescued the microbicidal phenotype caused by blocking the PERK pathway. Altogether, our study demonstrates that the Ixodes PERK pathway is activated by transmissible microbes and facilitates persistence in the arthropod by potentiating an Nrf2-regulated antioxidant environment. IMPORTANCE Recent advances demonstrate that the tick immune system recognizes and limits the pathogens they transmit. Innate immune mediators such as antimicrobial peptides and reactive oxygen/nitrogen species are produced and restrict microbial survival. It is currently unclear how pathogens remain in the tick, despite this immune assault. We found that an antioxidant response controlled by the PERK branch of the unfolded protein response is activated in ticks that are persistently infected with Borrelia burgdorferi (Lyme disease) or Anaplasma phagocytophilum (granulocytic anaplasmosis). The PERK pathway induces the antioxidant response transcription factor, Nrf2, which coordinates a gene network that ultimately neutralizes reactive oxygen and nitrogen species. Interfering with this signaling cascade in ticks causes a significant decline in pathogen numbers. Given that innate immune products can cause collateral damage to host tissues, we speculate that this is an arthropod-driven response aimed at minimizing damage to “self” that also inadvertently benefits the pathogen. Collectively, our findings shed light on the mechanistic push and pull between tick immunity and pathogen persistence within the arthropod vector.